Problem-based learning model assisted by google meet for parabolic motion topic to improve student learning outcomes - Wahyuni D. Sumayow; Trisnawaty Junus Buhungo; Ritin Uloli; Supartin Supartin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This research aims to produce quality physics learning tools using the Problem Based Learning (PBL) learning model. The study was conducted at a public senior high school (SMA Negeri 1 Tapa), Gorontalo, Indonesia. The device was developed using the 4D development model developed by Thiagarajan and Semel. The research results on the device show that the developed device is of high quality. Learning tools are said to be valid for use with little revision. It can be seen based on the average validation results of 3.5 to 3.6. The effectiveness of learning devices is seen in the increase in student learning outcomes. It consists of the cognitive domain from the first meeting until the second meeting. It obtained N Gain 0.54 with N Gain criteria moderate, in the attitude domain with an average percentage of 81.77%. The results of observing student activities during two meetings: 71.80% with good criteria. The psychomotor aspects with an average percentage of 80.36%, and the practicality of the developed devices seen from the observation sheet on the implementation of learning 84.78%, as well as teacher response questionnaires and student response questionnaires with an average the percentage of 79.88% and 84.80% got a positive response. There is an influence on student learning outcomes after the problem-based learning model is set with the help of the google meet application on parabolic motion material in the development of learning devices.